Landscape of Globally Minded Leadership Development for Public Servants - Ito Tsumagari, Maki (Indonesian Association for Public Administration, 2025)
This study aimed to unravel how far the concept of leadership development for agility has gone into the curriculum of higher education institutions (HEI) as an indication of their preparedness for educating public servants in the volatile, uncertain, complex, and ambiguous (VUCA) policy environment of today. A qualitative, systematic analytical method was adopted by referencing the public policy and administration schools of the world's top 100 ranked universities in The Times Higher Education World University Overall Rankings 2024. The results were categorized into three executive programs with the potential for leadership enhancement through customized arrangements, two executive programs with the label of